Ore mineralogy and silver distribution at the Rävliden N volcanogenic massive sulphide deposit, Skellefte district, Sweden - Johansson, Simon (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2017)
The Rävliden North deposit (Rävliden N) is a volcanogenic massive sulphide (VMS) deposit in the western part of the Skellefte district, northern Sweden. The district is one of Sweden’s major metallogenic provinces with a significant amount of VMS deposits. The Rävliden N deposit, discovered in 2011, contains copper, zinc, lead, silver and subordinate gold and occurs close to the largest VMS deposit in the district, the Kristineberg deposit, which has been mined for more than 70 years. The purpose of this master thesis is to study the composition, mineralogy and paragenetic relationships in different types of sulphide mineralization from the Rävliden N deposit. Emphasis is placed on characterizing the distribution and paragenetic relationships of silver-bearing minerals. The methods include core logging, sampling and mineralogical studies through light optical microscopy (LOM), scanning electron microscopy (SEM) and quantitative evaluation of mineralogy by scanning electron microscopy (QEMSCAN). Lastly, electron microprobe analysis (EMPA) was used to determine the chemical composition of silver-bearing minerals and sulphides. Mineralization types studied include 1: the main massive to semi-massive sulphide mineralization, 2: stratigraphically underlying stringer mineralization and 3: local, vein- and/or fault-hosted silver-rich mineralization in the stratigraphic hanging wall. The massive to semi-massive sulphide mineralization is dominated by sphalerite with lesser galena and pyrrhotite. In contrast, the stringer mineralization is dominated by chalcopyrite and pyrrhotite. The major minerals show evidence of a coeval formation and textural as well as structural evidence suggest that ductile deformation has affected the mineralization types. Notable evidence includes ball-ore textures, accumulation of minerals in pressure shadows and brittle fracturing of competent arsenopyrite and pyrite porphyroblasts and infilling by more incompetent sulphide minerals. The silver-bearing minerals identified are commonly ...